Awareness, Use, and Perceptions of Biodiesel by Belgian and American College Students - Donald M. Johnson; Leslie D. Edgar (Journal of International Agricultural and Extension Education, 2014)
Biodiesel is a renewable liquid transportation fuel with potential to extend petroleum supplies and reduce tailpipe emissions of particulate matter, unburned hydrocarbons, andcarbon monoxide (CO)and reduce life-cycle carbon dioxide (CO2)emissions relative to petroleum diesel.However, little is known about how various groups, eitherinternationally or domestically, view biodiesel.This study examined Belgian and Americancollege students’ awareness, use, and perceptions of biodiesel.A higher percentage of Belgian students versus American students reported driving diesel automobiles (60%and 17%, respectively) and being aware of biodiesel (100%and 86%, respectively).However, only 4% of either Belgian or Americanstudents had purchased biodiesel.Belgianstudents were undecidedand Americanstudents slightly agreed there were renewable and environmental benefits ofbiodieseluse.Both Belgian and Americanstudents were undecided about biodiesel quality, with Belgian students being more uncertain.Belgian and Americanstudents were also undecidedif there were negative externalities associated with biodiesel.Both groups tended to agree that continued long-term reliance on fossil fuels is not sustainable; however, Belgian students agreed more strongly than Americanstudents.While there were significant differences between Belgian and Americanstudents, both groups were largely undecided about biodiesel quality and the food and economic consequencesof biodiesel production and use; differences were primarily in the degree of uncertainty.Both groups (especially Belgian students) were concerned about continued reliance on fossil fuels.Given the low level of use and the high degree of uncertainty, efforts should be made to educate Belgian and Americancollege students about biodiesel
Keywords: Biodiesel; Perceptions; Survey; Belgium; United States